2010
DOI: 10.1111/j.1365-2761.2010.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Simple and direct detection of Aeromonas hydrophila infection in the goldfish, Carassius auratus (L.), by dot blotting using specific monoclonal antibodies

Abstract: A combination of eight isolates of Aeromonas hydrophila was used to produce monoclonal antibodies (MAbs). Ten different groups of MAbs specific to Aeromonas were selected. The first five groups of MAbs demonstrated high specificity and bound to only one or two isolates of A. hydrophila. The sixth and the seventh groups of MAbs were A. hydrophila specific. They recognized seven of eight A. hydrophila isolates (AH1, 2, 3, 4, 5, 6, 8); however, the MAb in the seventh group also showed cross-reactivity to one isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Also, they showed specificity to three inner membrane proteins (10, 25 and 37 kDa) and two cytoplasm proteins (15 and 20 kDa) (Figure 4). The study showed a molecular mass of 10 kDa which was also described by Longyant et al (2010) and is compatible with a lipopolysaccharide. Poobalane et al (2008) described two bands of 25 and 37 kDa as components of the bacterial membrane, which were purified from virulent isolates of A .…”
Section: Introductionsupporting
confidence: 85%
“…Also, they showed specificity to three inner membrane proteins (10, 25 and 37 kDa) and two cytoplasm proteins (15 and 20 kDa) (Figure 4). The study showed a molecular mass of 10 kDa which was also described by Longyant et al (2010) and is compatible with a lipopolysaccharide. Poobalane et al (2008) described two bands of 25 and 37 kDa as components of the bacterial membrane, which were purified from virulent isolates of A .…”
Section: Introductionsupporting
confidence: 85%
“…The virulence of the isolate A. veronii CAV-134 could be associated with the virulence gene Aha1 (major adhesion). A. veronii infection is a growing problem in cultured goldfish causing major economic losses in China (Longyant et al, 2010;Yang, 2013;Song et al, 2009;Hu et al, 2008;Xu et al, 2006).…”
mentioning
confidence: 99%
“…Various biochemical tests to identify the bacteria were performed in a conventional format. The origins and sources of the 41 Aeromonas isolates tested are shown in Table 1 Verification of Aeromonas spp.-A monoclonal antibody (MAb) developed in our laboratory and designated AH-396 was used to verify the bacteria in the genus Aeromonas (Longyant et al 2010), and an MAb designated AC-4A3 (unpublished data) was used to verify A. caviae. Briefly, bacterial cultures grown on tryptic soy agar (TSA; Table 1) were harvested and resuspended in phosphate-buffered saline (PBS) at pH 7.2, heat-killed at 60 • C for 1 h, and adjusted to an optical density at 600 nm equal to 1 (approximately 10 9 CFU/mL); finally, this suspension was diluted 10 times (10 8 CFU/mL).…”
Section: Methodsmentioning
confidence: 99%